Exploration of Online Doctor of Nursing Practice Students' Perceptions of Effective Teaching Methods Using the Critical Incident Technique. Issue 6 (3rd November 2022) - Robb, Meigan; Spadaro, Kathleen C.
Abstract : Background: The online learning environment presents unique challenges for engaging students in the learning process. Current research is limited regarding online doctor of nursing practice (DNP) students' perceptions of effective faculty involvement related to their engagement in learning. Purpose: This qualitative study explored DNP students' perceptions of effective methods used by faculty to help them learn and be engaged in the asynchronous online classroom. Methods: The Community of Inquiry (COI) framework provided the theoretical support for this study. The critical incident technique was used to explore DNP students' perceptions of effective methods used by faculty teaching in an asynchronous online program. Perceptions of effective methods were analyzed using the inductive approach of thematic analysis. Results: Three themes emerged from the data analysis: providing clarity, staying on track, and making it personalized. Conclusions: Findings suggest nurse educators should follow the COI framework to establish teacher presence and promote student engagement in online courses.